Analisis Peran Program Zakat Community Development BAZNAS Kota Samarinda Dalam Mengurangi Kemiskinan di Samarinda - Tikawati Tikawati; Eka Dwi Lestari (Al-Tijary, 2019)
This research was motivated by the activities of the Zakat Community Development program carried out by the BAZNAS of Samarinda City in the Loa Kumbar area of Loa Buah Village in Samarinda which aims to prosper the community or empowerment programs based on reducing poverty. The research is empirical research (field research), the data sources in this study were primary data obtained from field assistants and assistants from BAZNAS Samarinda.while the Respondents in this study were Kelurahan, RT, community leaders and field assistants and assistants from BAZNAS Samarinda and members. While the data collection techniques used were observation, interview and documentation. After the data was collected, then analyzed using qualitative methods. The findings in the field are, the driving factor of the implementation of the ZCD program in the Loa Kumbar region is that there are many people who do not have jobs, almost 70% of the population in the region are underprivileged and BAZNAS wants to encourage community self-help. The inhibiting factors in implementing the program were the late arrival of funds, facilitators who were still very minimal, communication gaps and the type of development of inappropriate activities. While the changes that have taken place in the Loa Kumbar region are facilities such as roads, mosques, schools, aquaculture, livestock and fisheries, free health programs such as mass circumcision and medical treatment.This program is very helpful for the Loa Kumbar community to become more prosperous.